2015
DOI: 10.1590/so100-720320150005361
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an illustrated home exercise guide on promoting urinary continence during pregnancy: a pragmatic randomized clinical trial

Abstract: ResumoOBJETIVO: Avaliar a efetividade de um manual de orientação de exercícios domiciliares (MOED) para o assoalho pélvico (AP) na promoção da continência urinária em gestantes primigestas. MÉTODOS: Ensaio clínico com 87 participantes, avaliadas 6 vezes durante a gestação e divididas aleatoriamente em 3 grupos: Grupo supervisionado (Gsup), que praticou exercícios com supervisão; Grupo observado (Gobs), que praticou exercícios sem supervisão, e Grupo referência (Gref), que não praticou exercícios. Incontinência… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 23 publications
0
10
0
3
Order By: Relevance
“…One study compared supervised PFMT with unsupervised PFMT and found no difference in urinary incontinence either during pregnancy or postpartum (12‐month follow‐up). The pelvic floor muscle strength was assessed in five trials, with three studies reporting a strength increase in the intervention group. The studies that analyzed anal incontinence did not demonstrate differences between the groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One study compared supervised PFMT with unsupervised PFMT and found no difference in urinary incontinence either during pregnancy or postpartum (12‐month follow‐up). The pelvic floor muscle strength was assessed in five trials, with three studies reporting a strength increase in the intervention group. The studies that analyzed anal incontinence did not demonstrate differences between the groups.…”
Section: Discussionmentioning
confidence: 99%
“…The strength of the pelvic floor muscles can decrease during pregnancy and after delivery, owing to physiological processes and changes in the anatomical position of the pelvis and in the shape of the pelvic floor muscles. This decrease in muscle strength facilitates the appearance of musculoskeletal alterations, leading to urinary incontinence, perineal laceration, and dyspareunia …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prevalence of UI in Pakistan is estimated to be 45% in pregnant and 10.6% in postpartum women [4,5]. The annual cost in the treatment of UI in United States (US) range from 16-65 billion dollars [6].…”
Section: Introductionmentioning
confidence: 99%
“…It has no reported side effects, is less time consuming and is cost effective. ICS advises PFMEs as the first line treatment for SUI [6].…”
Section: Introductionmentioning
confidence: 99%